Hydrothermal and mechanochemical synthesis of crystalline CaCO - J Skubiszewska-Zięba; B Charmas; H Waniak-Nowicka (Adsorption Science & Technology)
Mechanochemical and microwave-assisted hydrothermal (MicroWave Treatment [MWT]) procedures were applied to prepare crystalline CaCO 3 . Mechanochemical process was carried out at different speeds of rotation (500 or 850 rpm/min), different duration times (30 or 60 min) and in the aqueous suspensions or in dry state. MWT synthesis was conducted in a saturated water vapour or under the layer of water. The crystalline and porous structures of the prepared samples as well as their morphology were investigated using N 2 adsorption, X-ray diffraction and scanning electron microscopy methods. As a result, the calcium carbonate samples in the form of calcite were obtained. The materials prepared by the mechanochemical route performed in the aqueous suspension are characterized by smaller crystallite sizes as compared to those obtained without the addition of water. The samples obtained hydrothermally have the largest size of crystallites. Powders prepared by energetical milling possess higher values of specific surface area in relation to the parameter for those synthesized hydrothermally. In the process of hydrothermal treatment, macroporous structure of the prepared materials is created. With the increasing specific surface area of the sample, the size of the crystallites decreased.